(untitled) (Journal of the College of Basic Education, 2022)
Muslims cared a lot about the architecture of mosques, and that stemmed from the fact that they saw the Prophet Muhammad, may God bless him and grant him peace, interested in the mosque and its architecture, so the first step he took was to build the mosque in the new state in Medina, but due to the state’s instability due to strife, the trend in mosque architecture was not complete except in The time of the Umayyads due to security stability and their influence on Roman architecture in the Levant.